Strengthening Governance and Institutions in MENA : Issues and Priorities - Heidenhof, Guenter (World Bank, Washington, DC, 2014)
Governance has been an explicit part of the Bank s developmental agenda since the latter part of the 1990s, though elements of good governance have always played a role in the institution s work on development. These ranged from project focused work on financial management and procurement to the various sector governance components embedded in many of the Bank s adjustment and sector operations since the 1980s. More recently, the Bank has evolved towards a more explicit acknowledgment that inefficiencies and weaknesses in the institutional environment have a direct impact on the achievement and the quality of development results.